Strategic human resource management and performance in public hospitals in Ethiopia - Gile, Philipos Petros; van de Klundert, Joris; Buljac-Samardzic, Martina (Frontiers in Public Health, 2022)
Background Ethiopian public hospitals struggle to meet health care needs of the Ethiopian population, in part because of the persistent human resources crisis. The health reforms and tight human resource management (HRM) regulation of the government have resulted in limited progress toward addressing this crisis. This study aims to analyze how the strategic HRM practices adopted by Ethiopian public hospitals influence employee outcomes, organizational outcomes, and patient outcomes. Methods Structured interviews were conducted with 19 CEOs and HR managers from 15 hospitals. Four focus groups were also conducted, with 38 participants (professionals and line managers). The transcripts were thematically analyzed using ATLAS.ti 8. Deductive coding was used based on the Contextual SHRM framework, while remaining open for codes that emerged. Results Intended HR practices are influenced by mandatory strict government regulations. Nevertheless, some room for self-selected (bundles of) HR practices is perceived by hospitals. Employees perceive that governmental steered HR practices may not match its intentions due to implementation issues, related to lack of support and skilled management and HR professionals. These problems are leading to dissatisfaction, demotivation, moonlighting and turnover of skilled professionals and perceived to consequently negatively influence performance (i.e., patient satisfaction and waiting time). Conclusions There are considerable contextual challenges for SHRM in Ethiopian public hospitals. Hospital management can benefit from having more leeway and from exploiting it more effectively to improve actual and perceived strategic human resource management practices. Adoption of commitment based practices, in addition to mandatory control oriented practices can help to motivate and retain health care professionals and consequently improve outcomes.